Enhancing preservice teachers’ metacognition and critical thinking through the ERIC - Darmawan, Ericka; Ramadani, Shefa Dwijayanti; Normawati, Afi; Krisma, Dita Aldila; Admawati, Harsi; Agustyaningrum, Nina (Indonesian Journal of Educational Development (IJED), 2025)
Metacognitive and critical thinking skills are essential skills for being an effective learner. However, the results of previous studies indicate that these two skills in preservice teachers still require improvement. This research aimed to investigate the potential impact of the Exploring-Resuming Integrated Criticizing (ERIC) learning strategy on enhancing the metacognitive and critical thinking skills of preservice teachers. The study employed a quasi-experimental research design with a pretest and post-test component. The research population consisted of all biology education students at a university in Magelang City, Central Java, Indonesia. The sample consisted of 54 students from two classes enrolled in Plant Physiology, selected via cluster random sampling. Data on metacognitive and critical thinking skills were collected through pretest and posttest essay assessments. The data were analyzed using Analysis of Covariance (ANCOVA). The results of this study showed that the ERIC learning strategy has a significant impact on the preservice teachers’ metacognitive and critical thinking skills. We found that implementing ERIC learning led to higher metacognitive and critical thinking skills than those taught with a traditional approach. The research results recommend that ERIC be implemented as an active learning strategy to encourage the development of metacognitive and critical thinking skills.